Life Course Pathways From Adverse Childhood Experiences to Adult Physical Health: A Structural Equation Model. (February 2019) - Nurius, Paula S.; Fleming, Christopher M.; Brindle, Eleanor
Objective: This study examines pathways from adverse childhood experiences (ACEs) to physical health, directly and indirectly through lower income, health risk behaviors, social support, and adult adversity within a theoretical framework postulating stress proliferative and biological trajectories of cumulative adversity.Method: Data were obtained from 12, 549 adult respondents of a state Behavioral Risk Factor Surveillance System survey. Multigroup structural equation modeling elucidated pathways differentiated by sex and age (older/younger than 45).Results: Good model fit was achieved in each test, indicating consistency with stress theorizing that ACEs significantly contribute to poorer physical health through direct and mediated paths. Younger adults evidenced direct ACE pathway to poor health suggesting early biological erosion, whereas paucity of social support among older adults was directly associated.Discussion: Findings indicate that stress process roles in eroding physical health and experience of wellness. Addressing early adversity is an important strategy toward reducing preventable health problems.